Analisis Current Ratio dan Return on Assets Dalam Menilai Price Earning Ratio Pada PT. Indofood Sukses Makmur.Tbk Periode Tahun 2016 – 2020 - Suratman Hadi Priyatno; Dwi Sinta Sumarningsih (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2022)
This study aims to find out how the Current Ratio and Return On Assets (ROA) in assessing the Price Earning Ratio (PER) with the research object of PT Indofood Sukses Makmur, Tbk. Data is taken from financial reports for the 2016-2020 period. This study uses a qualitative descriptive method consisting of three variables, namely the Current Ratio and Return On Assets (ROA) as independent variables and the Price Earning Ratio (PER) as the dependent variable. Data analysis using case studies (non-hypothesis). Based on the results of data analysis, shows that the average current ratio per year as a whole is 134.85%, this condition is included in the unfavorable category based on industry average standards. For an average return on assets (ROA) per year of 5.76%, this condition is included in the good category based on industry average standards. Then from the results of the discussion, the current ratio in assessing the price earning ratio (PER) is 10.75% and the return on assets (ROA) in assessing the price earning ratio (PER) is 2.50%. For the current ratio and return on assets (ROA) in assessing the price earning ratio (PER) jointly or simultaneously, the average for the last 5 years, namely the 2016-2020 period, contributed 13.25% and the rest was contributed by other factors which were not examined in this study. Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana Current Ratio dan Return On Assets (ROA) dalam menilai Price Earning Ratio (PER) dengan objek penelitian adalah PT Indofood Sukses Makmur, Tbk. Data diambil dari laporan keuangan periode 2016-2020. Penelitian ini menggunakan metode deskriptif kualitatif yang terdiri dari tiga variabel yaitu current ratio dan return on assets (ROA) sebagai variabel bebas dan price earning ratio (PER) sebagai variabel terikat Analisis data menggunakan studi kasus (non-hipotesis). Berdasarkan hasil analisis data menunjukkan bahwa rata-rata current ratio per tahun secara keseluruhan sebesar 134,85%, kondisi ini termasuk dalam kategori kurang baik berdasarkan standar rata-rata industri. Untuk rata-rata return on assets (ROA) per tahun sebesar 5,76% kondisi ini termasuk dalam kategori baik berdasarkan standar rata-rata industri. Kemudian dari hasil pembahasan current ratio dalam menilai price earning ratio (PER) sebesar 10,75% dan return on assets (ROA) dalam menilai price earning ratio (PER) sebesar 2,50% Untuk current ratio dan return on aset (ROA) dalam menilai price earning ratio (PER) secara bersama-sama atau secara simultan rata-rata 5 tahun terakhir yaitu periode 2016-2020 memberikan kontribusi sebesar 13,25% dan sisanya disumbang oleh faktor lain yang tidak diteliti dalam penelitian ini